The Importance of N186 in the Alpha-1-Antitrypsin Shutter Region Is Revealed by the Novel Bologna Deficiency Variant - Ronzoni, Riccardo; Ferrarotti, Ilaria; D’Acunto, Emanuela; Balderacchi, Alice M.; Ottaviani, Stefania; Lomas, David A.; Irving, James A.; Miranda, Elena; Fra, Annamaria (International journal of molecular sciences, 2021)
Alpha-1-antitrypsin (AAT) deficiency causes pulmonary disease due to decreased levels of circulating AAT and consequently unbalanced protease activity in the lungs. Deposition of specific AAT variants, such as the common Z AAT, within hepatocytes may also result in liver disease. These deposits are comprised of ordered polymers of AAT formed by an inter-molecular domain swap. The discovery and characterization of rare variants of AAT and other serpins have historically played a crucial role in the dissection of the structural mechanisms leading to AAT polymer formation. Here, we report a severely deficient shutter region variant, Bologna AAT (N186Y), which was identified in five unrelated subjects with different geographical origins. We characterized the new variant by expression in cellular models in comparison with known polymerogenic AAT variants. Bologna AAT showed secretion deficiency and intracellular accumulation as detergent-insoluble polymers. Extracellular polymers were detected in both the culture media of cells expressing Bologna AAT and in the plasma of a patient homozygous for this variant. Structural modelling revealed that the mutation disrupts the hydrogen bonding network in the AAT shutter region. These data support a crucial coordinating role for asparagine 186 and the importance of this network in promoting formation of the native structure.